Animal Models to Investigate the Pathogenesis of Rheumatic Heart Disease - Rush, Catherine M.; Govan, Brenda L.; Sikder, Suchandan; Williams, Natasha L.; Ketheesan, Natkunam (Frontiers in Pediatrics, 2014)
Rheumatic fever (RF) and rheumatic heart disease (RHD) are sequelae of group A streptococcal (GAS) infection. Although an autoimmune process has long been considered to be responsible for the initiation of RF/RHD, it is only in the last few decades that the mechanisms involved in the pathogenesis of the inflammatory condition have been unravelled partly due to experimentation on animal models. RF/RHD is a uniquely human condition and modelling this disease in animals is challenging. Antibody and T cell responses to recombinant GAS M protein (rM) and the subsequent interactions with cardiac tissue have been predominantly investigated using a rat autoimmune valvulitis model. In Lewis rats immunized with rM, the development of hallmark histological features akin to RF/RHD, both in the myocardial and in valvular tissue have been reported, with the generation of heart tissue cross reactive antibodies and T cells. However, studies of cardiac function are more challenging in such a model. Recently a Lewis rat model of Sydenham’s chorea (SC) and related neuropsychiatric disorders has also been described. Rodent models are very useful for assessing disease mechanisms due to the availability of reagents to precisely determine sequential events following infection with GAS or post-challenge with specific proteins and or carbohydrate preparations from GAS. However, studies of cardiac function are more problematic in such models. In this review an historical overview of animal models previously used and those that are currently available will be discussed in terms of their usefulness in modelling different aspects of the disease process. Ultimately, cardiologists, microbiologists, immunologists and physiologists may have to resort to diverse models to investigate different aspects of RF/RHD.